2018
DOI: 10.1186/s41936-018-0060-4
|View full text |Cite
|
Sign up to set email alerts
|

Hepato-morpholoy and biochemical studies on the liver of albino rats after exposure to glyphosate-Roundup®

Abstract: Background: The object of this work was to evaluate of the hepatic effects of the herbicides glyphosate-Roundup® by different doses in both sexes of albino rats. Methods: Forty animals divided into four groups with ten animals for each (both sexes) were treated orally with vehicle (controls) and 25, 50, and 100 mg/kg bwt of glyphosate-Roundup® (treated groups) for 15 days daily. Results: The most conspicuous changes occurred on the liver treated groups due to glyphosate toxicity were the increase of enzymes ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 26 publications
(30 reference statements)
2
11
0
Order By: Relevance
“…In the present study, leukocytic infiltration was observed in the core of the villi and between crypts, a finding that agrees with the observations of a previous study in the liver of rats exposed to glyphosate (Saleh et al, 2018). Walter & Isreal (1974) suggested that such leukocytic infiltration might be due to the presence of necrotic cells, which act as disturbing substances that catch the inflammatory cells.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, leukocytic infiltration was observed in the core of the villi and between crypts, a finding that agrees with the observations of a previous study in the liver of rats exposed to glyphosate (Saleh et al, 2018). Walter & Isreal (1974) suggested that such leukocytic infiltration might be due to the presence of necrotic cells, which act as disturbing substances that catch the inflammatory cells.…”
Section: Discussionsupporting
confidence: 93%
“…Similar results were reported by Samanta et al (2016b), who found deformation in the RER and fatty deposition in the stomach of freshwater teleostean fish (Heteropneustes fossilis) after glyphosate treatment. Samanta et al (2016b) and Saleh et al (2018) observed the deposition of lipid droplets in fish and rats exposed to glyphosate, respectively. These observations are in agreement with the present results on the villi epithelium.…”
Section: Discussionmentioning
confidence: 99%
“… 13 , 32 Hepatic inflammation characterized by increasing numbers of mononuclear cells and proliferation of collagen fibres in the liver may be responsible for the increased serum ALP activity; in line with this, hepatic enzyme secretion is elevated following cholestasis in the presence of glyphosate-induced steatohepatitis. 33 36 Damage to the liver was expected to affect the functional capacity of the liver to synthesize proteins, thereby influencing serum total protein and albumin levels. However, chronic glyphosate exposure did not significantly affect these values, indicating that the compensatory synthetic capacity of the liver was sustained despite any toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…14 , 15 Hepatorenal protection by zinc was attributed to its antioxidant properties, 16 , 17 which might have promoted the integrity of cell membranes and reduced the impact of oxidative stress; this is considered to be the principal factor promoting toxic injury following glyphosate exposure. 3 , 4 , 6 , 7 , 30 , 33 , 47 In addition, the inflammatory effect induced by glyphosate 5 , 34 , 36 might be counteracted by the anti-inflammatory properties of zinc. 17 During a chronic toxicity study, zinc pretreatment may not be capable of preventing the metabolic effects of glyoxylate, a metabolite of glyphosate.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted by Saleh et al (2018) shows that many changes occurred in the treatment group, where there was an increase in the alanine aminotransferase and aspartate aminotransferase enzymes, cellular infiltration, a lot of nuclear degeneration, physical necrosis, cytoplasm and lipid deposition, increase in the number of collagen fibers, and an increase in the number of mast cells.…”
Section: Histopatology Of Organ Tissuementioning
confidence: 99%